PENGARUH DIAMETER NOZZLE DAN PANJANG CABLE TERHADAP CYCLE TIME PADA MESIN AUTOMATIC CABLE TERMINAL YANG DIMODIFIKASI - Ubaidillah, Muhammad; Dani, Agus (Otopro, 2025)
Automatic Cable Terminal Machine is an automatic machine used to cut and process electrical materials, this machine is used by automotive companies to make wiring harnesses. This machine is able to cut raw materials with high precision and optimal speed. In changing the nozzle this machine is modified from manual to semi-automatic to make the machine more optimal. Cycle time is the time required to complete one cycle of cutting operations, from preparation to completion. Cycle time efficiency is very important because it has a direct impact on productivity and production costs. Therefore, optimising cycle time is the main focus in machine research and modification. The purpose of this study is to determine the effect and interaction of nozzle change and cable length on cycle time on a modified Automatic Cable Terminal machine. The research method used was experimental by varying the independent variables of nozzle diameter (15mm, 17mm and 19mm) and cable length (1400mm, 2200mm and 3500mm) with factorial anova data processing method using statistical software. The results showed that the change of nozzle and cable length affected the cycle time and the combination of parameters resulted in an optimal cycle time with high desirability. Nozzle diameter of 15 and cable length of 1400 mm resulted in a cycle of 381.2 seconds with desirability almost close to 1 (0.943590) which indicates that this solution is very good.